2017
DOI: 10.1038/s41598-017-16537-5
|View full text |Cite|
|
Sign up to set email alerts
|

Phosphate-Solubilizing Bacteria Nullify the Antagonistic Effect of Soil Calcification on Bioavailability of Phosphorus in Alkaline Soils

Abstract: Phosphate-solubilizing bacteria (PSB) reduce the negative effects of soil calcification on soil phosphorus (P) nutrition. In this incubation study, we explored the ability of PSB (control and inoculated) to release P from different P sources [single super phosphate (SSP), rock phosphate (RP), poultry manure (PM) and farm yard manure (FYM)] with various soil lime contents (4.78, 10, 15 and 20%) in alkaline soil. PSB inoculation progressively enriched Olsen extractable P from all sources compared to the control … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
66
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(70 citation statements)
references
References 69 publications
4
66
0
Order By: Relevance
“…It could be revealed that Mesorhizobium is useful as a reducing agent of the negative effects of soil calcification on soil P nutrition. The ability to produce IAA by tested strains can have direct effects on production of phytohormones, enzymatic activities, nitrogen accumulation in shoots and seeds, and plant biomass [56][57][58][59]. The isolated strains showed high catalase activity, similar to the observations made by Nakayama et al [60], which indicated that these isolates could…”
Section: Discussionsupporting
confidence: 62%
“…It could be revealed that Mesorhizobium is useful as a reducing agent of the negative effects of soil calcification on soil P nutrition. The ability to produce IAA by tested strains can have direct effects on production of phytohormones, enzymatic activities, nitrogen accumulation in shoots and seeds, and plant biomass [56][57][58][59]. The isolated strains showed high catalase activity, similar to the observations made by Nakayama et al [60], which indicated that these isolates could…”
Section: Discussionsupporting
confidence: 62%
“…It has been recently shown a relevant interaction in field between Calcium and P solubilization process. Phosphate‐solubilizing bacteria reduce the negative effects of soil calcification on soil phosphorus (P) nutrition .…”
Section: Introductionmentioning
confidence: 88%
“…Unambiguously, our results indicated that the inoculation with single or mix culture of PSP strains (ENPSB) were contributed to increase the amount of available phosphorus in the soil and this is well in agreement with results obtained by Liu et al (2014) who found that the highest level of available P and the greatest stimulation of plant height and dry weight were obtained in soils coinoculated with the three bacterial strains of phosphate dissolving bacteria. Shi et al (2017) and Adnan et al (2017) reported that the use of PSB strains increased P availability and reduced the negative effect of calcification on the soil.…”
Section: Discussionmentioning
confidence: 99%